1992
DOI: 10.1099/00222615-37-5-319
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Caco-2 cells as a model for enteric invasion by Campylobacter jejuni and C. coli

Abstract: Summary.A collection of 44 Campylobacter isolates (37 C. jejuni and seven C. coli) from children with colitis (21 strains) or watery diarrhoea (23 strains) was analysed for toxin production, association with HeLa cells, and invasion of differentiated Caco-2 cell cultures. There was no obvious association of clinical symptoms with species, biotype or enterotoxin production. All colitis strains and most of the isolates from watery diarrhoea were cytotoxic for Chinese hamster ovary cells. Measurements of bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
1
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 25 publications
7
119
1
3
Order By: Relevance
“…The data shown are the means of triplicate experiments. 13,15,20). In this study, kinetic analysis of C. jejuni invasion into INT-407 cells revealed that optimal invasion efficiency (percentage of the inoculum recovered as internalized at the end of the gentamicin treatment assay) was highest at the lowest MOI of 1 but that a maximal number of internalized C. jejuni was detected at 100 MOI.…”
Section: Discussionmentioning
confidence: 98%
“…The data shown are the means of triplicate experiments. 13,15,20). In this study, kinetic analysis of C. jejuni invasion into INT-407 cells revealed that optimal invasion efficiency (percentage of the inoculum recovered as internalized at the end of the gentamicin treatment assay) was highest at the lowest MOI of 1 but that a maximal number of internalized C. jejuni was detected at 100 MOI.…”
Section: Discussionmentioning
confidence: 98%
“…Quantitation data are summarized in Table 2. (B) To ensure equal amounts of bacteria in each sample, the corresponding bacterial pellets were probed with α-HtrA antibodies [35][36][37][38]. We are interested in characterizing bacterial and host factors involved in C. jejuni transmigration.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultivated in RPMI 1640 supplemented with 10% fetal bovine serum and 0.02% each penicillin and streptomycin at 37°C in 5% CO 2 . Bacterial invasion was determined by using a gentamicin protection assay (14). Briefly, cells were grown to approximately 80% confluence in 12-well tissue culture plates, and after three washes with Hanks balanced salt solution, the cells were infected with C. jejuni at a …”
Section: Methodsmentioning
confidence: 99%